Emerging Directions in Embedded and Ubiquitous Computing: EUC 2007 Workshops - TRUST, WSOC, NCUS, UUWSN, USN, ESO, and SECUBIQ, Taipei, Taiwan, December 17-20, 2007, Proceedings - Demko, Mieso K; Shih, Chi-Sheng; Li, Kuan-Ching (Springer, 2007)
This book constitutes the refereed proceedings of the EUC 2007 workshops held in conjunction with the IFIP International Conference on Embedded and Ubiquitous Computing, EUC 2007, in Taipei, Taiwan, in December 2007. The 69 revised full papers presented together with 4 invited papers were carefully reviewed and selected from about 200 submissions to the seven workshops. Topics covered by the workshops are trustworthiness, reliability and services in ubiquitous and sensor networks (TRUST 2007), system and software for wireless system-on-chip (WSOC 2007), network centric ubiquitous systems (NCUS 2007), ubiquitous underwater acoustic-sensor network (UUWSN 2007), RFID and ubiquitous sensor networks (USN 2007), embedded software optimization (ESO 2007), and security in ubiquitous computing (SecUbiq 2007).